2005
DOI: 10.21273/hortsci.40.7.2118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Irrigation Method and Scheduling on Patterns of Soil and Tree Water Status and Its Relation to Yield and Fruit Quality in Peach

Abstract: A 3-year study was done to determine the effects of furrow, microspray, surface drip, and subsurface drip irrigation on production and fruit quality in mature `Crimson Lady' peach [Prunus persica (L.) Batsch] trees. Furrow and microspray irrigations were scheduled weekly or biweekly, which is common practice in central California, while surface and subsurface drip irrigations were scheduled daily. Trees were maintained at similar water potentials following irrigation by adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 31 publications
(29 reference statements)
1
16
0
1
Order By: Relevance
“…1). Drip is well known to maintain higher soil water availability within the root zone than other methods of irrigation (Kruse et al, 1990), thereby reducing water stress between irrigations and increasing plant growth and production (e.g., see Bryla et al, 2005); however, growth and production may be inhibited if saturated soil conditions persist (Davies and Wilcox, 1984). Soil was often saturated and exceeded field capacity (i.e., greater than 30% soil water content) in our study when irrigation was applied at 100% to 150% ET c by drip and 150% ET c by sprinklers and microsprays.…”
Section: Resultsmentioning
confidence: 99%
“…1). Drip is well known to maintain higher soil water availability within the root zone than other methods of irrigation (Kruse et al, 1990), thereby reducing water stress between irrigations and increasing plant growth and production (e.g., see Bryla et al, 2005); however, growth and production may be inhibited if saturated soil conditions persist (Davies and Wilcox, 1984). Soil was often saturated and exceeded field capacity (i.e., greater than 30% soil water content) in our study when irrigation was applied at 100% to 150% ET c by drip and 150% ET c by sprinklers and microsprays.…”
Section: Resultsmentioning
confidence: 99%
“…Fallahi et al [149] concluded that water application through a drip system, calculated based on full ETc rate and adjusted for groundcover, results in major water saving and often improves yield and fruit quality when compared with full microjet sprinklers, achieving a water consumption reduction of about 1/3. Bryla et al [150] concluded that the most effective irrigation methods for increasing peach production are surface and subsurface drips. Through three growing seasons, these two methods increased the average fruit size, reduced the number of nonmarketable fruits, and improved the marketable yield by 9% to 22% over more traditional furrow or microspray irrigation methods.…”
Section: Irrigation Systemsmentioning
confidence: 99%
“…Bryla et al . () also reported a reduction in yield of peach under flood irrigation. Variations in fruit yield could be attributed to better growth, flowering and fruit setting under the drip irrigation system.…”
Section: Resultsmentioning
confidence: 86%